Do related party transactions matter for firm performance? LQ 45 firm perspective - Puspitasari, Nindya Farah Dwi; Solihat, Iis; Nisrina Sari, Nindhita (Institute of Computer Science (IOCS), 2023)
This study aims to provide empirical evidence regarding whether related party transactions (RPTs) are really a matter for company financial performance. It also investigates other possible factors that may influence firm performance such Covid 19 pandemic situation, company size and sales growth. The samples are obtained from companies recorded in the LQ 45 index in 2019 which were studied from 2018 to 2021. The results shows that RPTs do not significantly influence firm performance. This happens because companies do not rely on related party relationships in the sales or purchasing process. In addition, Covid 19 and company size have a significant negative impact on ROE and ROA. Whereas sales growth has a significant positive relationship on firm performance. This indicates that having a large asset investment does not guarantee an increase in the company's financial performance. A strategy that focuses on increasing sales will be more profitable